Molecular mechanisms of the anchang group prescription in treating radiation enteritis: network pharmacology analysis and experimental evidence - Liang, Wei; Li, Bo; Sun, Yuehong; Jia, Dapeng; Hu, Tingting; Huang, Rujing; Liu, Zhilong; Yang, Huan; Chen, Baocai; Yin, Xiaoming; He, Xinying; Sun, Yunchuan (Frontiers in Pharmacology, 2025)
BackgroundThe “Anchang” Group Prescription (ACZF), based on the traditional Bai Tou Weng Decoction and Si Jun Zi Decoction, has demonstrated clinical efficacy in alleviating symptoms of radiation enteritis (RE). Nevertheless, the precise active components and their underlying molecular mechanisms in ACZF’s effect on RE require further elucidation. This investigation seeks to delineate the active components and explore the molecular mechanisms by which ACZF mitigates RE, utilizing both network pharmacology and experimental approaches to provide a solid theoretical base for subsequent research and clinical applications.MethodsUtilizing network pharmacology, this research constructed a comprehensive “drug-active ingredient-target gene-disease” model leveraging resources such as TCMSP, SwissTargetPrediction, GeneCard, and OMIM. Cytoscape 3.8.2 along with the STRING database were instrumental in developing a protein-protein interaction (PPI) network for the identification of pivotal targets. Functional enrichment analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, were conducted via the DAVID database. Experimentally, a mouse model of RE was induced by X-ray exposure to assess the physiological and pathological responses. Parameters measured included body weight, survival rate, incidences of diarrhea, and hematochezia; histological assessments involved hematoxylin and eosin (H&E) and Masson’s trichrome staining to examine morphological alterations and collagen deposition in colonic tissues. Levels of cytokines such as interleukin-1β (IL-1β), IL-6, IL-10, and tumor necrosis factor-α (TNF-α) were quantified using enzyme-linked immunosorbent assays (ELISA). Additionally, immunohistochemistry (IHC) and Western blotting (WB) were employed to evaluate the expression of tight junction proteins zonula occludens-1 (ZO-1) and claudin-1, as well as proteins linked to the PI3K/AKT pathway.ResultsKey bioactive constituents of ACZF in treating RE include quercetin, kaempferol, isorhamnetin, and luteolin, with core target proteins such as SRC, STAT3, AKT, HSP90AA1, and EGFR. Involved signaling pathways include PI3K/AKT, RAP1, and MAPK. In vivo results revealed that mice treated with ACZF showed enhanced survival, increased body weight, and extended colon lengths compared to controls. Although Masson staining showed no significant differences, H&E staining indicated that radiation-induced mucosal damage, including extensive ulcer formation, inflammatory cell infiltration, crypt structure destruction, and epithelial layer injury, could all be ameliorated by ACZF. Notable reductions were observed in TNF-α, IL-1β, and IL-6 levels, while IL-10 levels saw a significant rise. There was also a marked increase in the expression of ZO-1 and claudin-1. WB analyses demonstrated the activation of the PI3K/AKT pathway in RE, which was significantly curtailed by ACZF, lowering phosphorylation levels within the colonic tissues. Concurrent administration of the PI3K activator YS-49 with ACZF reversed the inhibitory effects on the PI3K/AKT pathway and mitigated impacts on epithelial TJ protein expression and inflammatory cytokine levels, highlighting the critical role of the PI3K/AKT pathway in mediating ACZF’s therapeutic effects in RE.ConclusionACZF alleviates RE by inhibiting PI3K/AKT activation, reducing inflammation, and preserving intestinal mucosal integrity.